Patrimônio cultural religioso e negociação da identidade do imigrante italiano da Quarta Colônia Imperial de Silveira Martins e região central do Rio Grande do Sul - Barichello, Cesar Augusto (2010)
The relationship established between the religious and cultural heritage and the process of identity negotiating of Italian immigrant justify the importance of investigating the subject of this research. The problem can be summarized in the following question: how was traded the identity of Italian immigrant from the cradle of the Quarta Colonia Imperial de Imigração Italiana in the central region of Rio Grande do Sul? The working hypothesis is that the negotiation of immigrants identity took place through religious devotion and can be evidenced by the religious heritage (churches, chapels and iconography) and the introduction of devotions. The methodology of a qualitative approach seeks to contemplate the complexity of the research problem, in which the research process (goals, methods and data) emerges from the study context, and interpreting the results comes as a total reflection based on the description of a phenomenon in a context. Field research and source identification were carried out in three distinct stages: the first was the identification of churches, chapels and beliefs taking to support the different lines of territorial settlement of the colonists; the second was the observation of religious everyday life lived by descendant of Italian immigrants in the various lines; and the third in the use of the technique of interviews conducted with community members of Silveira Martins which have an involvement with religious movements or could contribute to elucidate the perceptions, and their own perception, regarding the object under study. The objective of this study is to investigate the relationships developed between the religious heritage and the negotiation process of the identity in the Quarta Colônia Imperial de Silveira Martins and the central region of Rio Grande do Sul. The specific objectives are to identify churches, chapels, oratories, patron saints and religious devotions present in the lines of settlement of Silveira Martins immigrants; perform on-site observation during the course of the filós in the parish halls of the various chapels; investigate through interviews with community members, the source of the patron saints their possible links with ethnic groups and their specific meanings represented (churches and chapels, oratories) or symbolically (patron saints and devotions).